Suspension cell cultures of Panax vietnamensis as a biotechnological source of ginsenosides: growth, cytology, and ginsenoside profile assessment - Titova, Maria V.; Lunkova, Maria K.; Tyurina, Tatiana M.; Prudnikova, Olga N.; Popova, Elena V.; Klychnikov, Oleg I.; Metalnikov, Pavel S.; Ikhalaynen, Yuri A.; Vasileva, Elizaveta N.; Rodin, Igor A.; Nosov, Alexander M. (Frontiers in Plant Science, 2024)
Panax vietnamensis is a valuable medicinal plant and a source of a broad spectrum of biologically active ginsenosides of different structural groups. Overexploitation and low adaptability to planation cultivation have made this species vulnerable to human pressure and prompted the development of cell cultivation in vitro as a sustainable alternative to harvesting wild plants for their bioactive components. Despite high interest in biotechnological production, little is known about the main factors affecting cell growth and ginsenoside biosynthesis of this species under in vitro conditions. In this study, the potential of cell cultures of P. vietnamensis as a biotechnological source of ginsenosides was assessed using six suspension cell lines that were developed from different sections of a single rhizome through a multi-step culture optimization process and maintained for over three years on media with different mineral salt base and varying content of auxins and cytokinins. These cell lines were evaluated for productivity parameters, cytological characteristics, and ginsenoside profiles. All lines demonstrated good growth with a specific growth rate of 0.1-0.2 day-1, economic coefficient of 0.31-0.70, productivity on dry weight (DW) of 0.30-0.83 gDW (Lday) -1, and maximum biomass accumulation varying from 10 to 22 gDW L-1. Ginsenosides of protopanaxadiol (Rb1, Rb2/Rb3, malonyl-Rb1, malonyl-Rb2/Rb3), oleanolic acid (R0, chikusetsusaponin IV) and ocotillol (vinaginsenoside R1) groups and their isomers were identified in cell biomass extracts using a combination of the reversed-phase ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-Orbitrap-MS/MS) and ultra-performance liquid chromatography-mass spectrometry (UPLC-TOF-MS). Chikusetsusaponin IV was identified in P. vietnamensis cell culture for the first time. These results suggest that suspension cell cultures of Vietnamese ginseng have high potential for the biotechnological production of biomass containing ginsenosides, particularly of oleanolic acid and ocotillol groups.